1995
DOI: 10.1148/radiology.195.1.7892495
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow: measurement with xenon-enhanced dynamic helical CT.

Abstract: This volumetric CBF mapping method is applicable in clinical practice because of the short examination time and acceptable radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Such techniques, which include Xe-enhanced CT, PET, and SPECT, can identify regional perfusion instability prior to treatment and ascertain the extent of improvement of functional perfusion following therapy. 60,62,74,108 Single photon emission CT, with and without acetazolamide/CO 2 vasodilatory challenge, is a particularly useful technique that assesses cerebrovascular reserve and helps to predict the likelihood of further disease progression. Occlusion of the major cerebral arteries in patients with moyamoya produces chronic hemodynamic stress.…”
Section: Diagnosismentioning
confidence: 99%
“…Such techniques, which include Xe-enhanced CT, PET, and SPECT, can identify regional perfusion instability prior to treatment and ascertain the extent of improvement of functional perfusion following therapy. 60,62,74,108 Single photon emission CT, with and without acetazolamide/CO 2 vasodilatory challenge, is a particularly useful technique that assesses cerebrovascular reserve and helps to predict the likelihood of further disease progression. Occlusion of the major cerebral arteries in patients with moyamoya produces chronic hemodynamic stress.…”
Section: Diagnosismentioning
confidence: 99%
“…To determine the optimal targets for revascularization procedures as well as for postoperative follow-up, CBF studies with the use of Xe-CT, SPECT, or PET have been shown to be of high clinical value. [3][4][5][6][7] However, these methods are associated with ionizing radiation, which should be minimized or avoided whenever possible and especially in young patients. Recently, interest in MR imaging techniques for CBF assessment has grown, and initial evaluation of these techniques has been undertaken in patients with Moyamoya disease.…”
mentioning
confidence: 99%
“…Cerebral blood flow techniques are very useful in diagnosis and management of MMD, which include Xe-enhanced CT, PET and SPECT that assess cerebrovascular reserve as well as disease progression [32][33][34].…”
Section: Moyamoya Diseasementioning
confidence: 99%